PENENTU PERILAKU BERINVESTASI - Widayat, Widayat (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
Modern Financial theory based on assumption that individual investment decision is rationaly. Occurance anomalies indicate that investment choice is not always rational. Irrationality in the field of investment tend to develop the theory of behavior investment. The theory of finance behavior catalyzed by sociology, psychology and also finance. According to this theory, economics decision and investment decision as a integrated behavior, affected by many antecendence variables. Financial literacy, socio demography aspect, attitude toward risk are influence investment behavior. Besides external factor for example economics condition also affecting behavior of investment.